The Effect of Using Frontloading Strategy in Teaching Reading Comprehension at The Seventh Grade Students of SMP N 10 Bengkulu In The Academic Year of 2018/2019 - Nani Windiarti; Arasuli .; Rudi Afriazi (Universitas Bengkulu, 2019)
This study was conducted to find out the effect of using frontloading strategy in teaching reading comprehension at the seventh grade students of SMPN 10 Bengkulu. This research was a quasi experimental research that is one short experiment which used post-test only. The population of this research were the seventh grade students of SMPN 10 Bengkulu there are 180 students. The sample of this research were 57 students from two classes; the experimental class and control class. The experimental class was treated by using frontloading strategy, while the control class was taught by conventional strategy. The two classes have similar ability in English based on the scores of mid-term examination. In experimental class there was a significant positive effect towards the students reading comprehension (it was found that the t-count 2.047 while t-table was 1.676). T-count was bigger than t-table (2.047<1.676). Based on those results, it can be assumed frontloading strategy was effective in increasing students’ reading comprehension.